Periodic self-rostering in shift work: correspondence between objective work hours, work hour preferences (personal fit), and work schedule satisfaction - Michael Ingre; Torbjörn Åkerstedt; Mirjam Ekstedt; Göran Kecklund (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: The main objective of the present study was to investigate relative personal fit as the association between rated needs and preferences for work hours, on the one hand, and actual work hours, on the other hand, in three groups (hospital, call-center, and police) working with periodic self-rostering. We also examined the association between personal fit and satisfaction with the work schedule and preference for a fixed and regular shift schedule, respectively. METHODS: We collected questionnaire data and objective work hour data over 6-12 months from the computerized self-rostering system. The response rate of the questionnaire was 69% at the hospital and call-center and 98% among the police. In total, 29 433 shifts for 285 shift workers were included in the study. Data was analyzed by means of mixed ANOVA, Kendal tau correlations and ordinal (proportional odds) logistic regression. RESULTS: The results show that evening types worked relatively more hours during the evening and night hours compared to morning types as an indication of relative personal fit. Relative personal fit was also found for long shift, short rest, and morning-, evening- and night-shift frequency, but only personal fit related to morning, evening and night-shift was associated with satisfaction with work hours. Reported conflicts at the workplace about work hours and problems with lack of predictability of time for family/leisure activities, was associated with poor satisfaction and a preference for a fixed shift schedule. CONCLUSIONS: The present study shows that periodic self-rostering is associated with relative personal fit, in particular with respect to night, evening, and morning work. Personal fit seems to be associated with satisfaction with work hours and may be a moderator of tolerance to shift work exposure.